Refleksi Strategis Pengembangan Madrasah: Praktik Inovatif di Man 1 Pidie, Aceh - Amin, Khairul (LaKaspia, 2024)
This article is a reflective study that aims to describe the strategic development of madrasahs towards becoming innovative and high-achieving institutions, based on institutional experience at MAN 1 Pidie, Aceh. Employing a qualitative approach, data were gathered through reflective notes, participatory observations, and interviews. The study outlines the development strategy in five key stages: problem identification, planning, program formulation, implementation, and evaluation. The findings indicate that strategies developed collaboratively and based on real institutional needs have successfully increased school-wide engagement and resulted in several flagship programs, both in regular and non-regular categories. Programs such as elite classes, social outreach activities, and extracurricular initiatives have had a positive impact on student achievement and the public image of the madrasa. Nevertheless, some programs still require ongoing improvements to enhance their effectiveness and competitiveness. This study highlights the importance of institutional reflection and strategic governance in advancing innovation-based educational transformation in madrasahs. Abstrak Artikel ini merupakan studi reflektif yang bertujuan untuk mendeskripsikan strategi pengembangan madrasah menuju madrasah inovatif dan berprestasi berdasarkan pengalaman institusional di MAN 1 Pidie, Aceh. Menggunakan pendekatan kualitatif dengan sumber data dari catatan reflektif, observasi partisipatif, dan wawancara, artikel ini mengurai proses pengembangan dalam lima tahapan utama: identifikasi masalah, perencanaan, penyusunan program, implementasi, dan evaluasi. Hasil kajian menunjukkan bahwa strategi yang disusun secara kolaboratif dan berbasis kebutuhan nyata mampu meningkatkan keterlibatan warga madrasah dan menghasilkan sejumlah program unggulan, baik dalam kategori reguler maupun non-reguler. Program seperti kelas unggul, gerakan sosial, dan kegiatan ekstrakurikuler terbukti memberi dampak positif terhadap prestasi siswa dan peningkatan citra madrasah. Meskipun demikian, sejumlah program masih memerlukan perbaikan berkelanjutan agar lebih efektif dan berdaya saing. Studi ini menegaskan pentingnya refleksi internal dan tata kelola strategis dalam mendorong transformasi madrasah berbasis inovasi.